Assessment of the MRI and behavioral test results in focal cerebral ischemia reperfusion model in rat after separate and combined use of mouse-derived neural progenitor cells, human-derived neural progenitor cells and atorvastatin - Tahta, Alican; Izgi, Nail; Onder, Tugba Bagci; Erdag, Ece; Aras, Yavuz; Genc, Cetin (Turkish neurosurgery, 2018)
We aimed to assess the efficacy of Neural progenitor cell (NPC) transplantation in ischemic stroke, and to investigate whether atorvastatin enhances therapeutic potency of NPC after stroke. Focal cerebral ischemia-reperfusion model was performed by transient occlusion of middle cerebral artery. Rats were assigned randomly to receive intracerebral transplantation of mouse NPC alone (mNPC), human NPC alone (hNPC), mouse NPC plus oral atorvastatin (mNPC+A), human NPC plus oral atorvastatin (hNPC+A), oral atorvastatin alone, or intracerebral Dulbecco's Modified Eagle's medium injection (control group). Adhesive removal, rotarod, cylinder tests, and magnetic resonance imaging (MRI) were used for assessment of rats during 4 weeks. After sacrification on 28th day, rats were investigated by immunofluorescent staining. The hNPC and mNPC groups showed significantly improved functional outcome and reduced infarct area rate compared with control group. hNPC group had significantly better performance and lower infarct area rate than mNPC group. Addition of atorvastatin to stem cell therapy significantly improved functional outcome, despite it didn't affect the infarct area rate on MRI. Anti-inflammatory response in the infarcted area was higher in mNPC group. NPC transplantation significantly reduced the amount of microglia while they caused significant increase in the amount of astrocytes. CD8a+ T lymphocyte and granzyme B activities were not detected in none of the subjects. Both hNPC and mNPC treatments significantly improved functional outcome, and reduced infarct area rate after stroke. Atorvastatin enhanced the therapeutic potency of NPCs, including neurological improvement.